Empowering Digital Literacy in Islamic Boarding Schools: A Participatory Action Research Approach at Pondok Pesantren Sabilul Muttaqin - Syakur, Abd; Dainori, Dainori; Fitriyah, Rizka; Paisun, Paisun (STAI Miftahul ULa Nganjuk, 2024)
This community service project aimed to enhance digital literacy among the students of Pondok Pesantren Sabilul Muttaqin Daramista Lenteng Sumenep by implementing a Participatory Action Research (PAR) approach. The project focused on equipping students with critical digital skills to navigate the internet responsibly, create digital content, and engage with social media as tools for religious outreach. The training consisted of seminars on positive internet use, workshops on journalism and article writing, and sessions on digital content creation. The results of the intervention demonstrated a significant improvement in the students’ ability to evaluate digital content, produce well-structured articles, and manage digital platforms such as websites and social media accounts. Furthermore, the project fostered greater involvement of the Pesantren leadership and students in managing digital platforms for the dissemination of Islamic knowledge. The intervention’s success highlights the importance of digital literacy in educational institutions, especially in the context of Islamic education, where access to digital resources can enhance both learning and outreach. This study provides a model for integrating digital literacy into religious institutions and offers recommendations for expanding such initiatives to other Pesantren.